2021
DOI: 10.1109/access.2021.3112880
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Data Models for the Big Data Problem

Abstract: Nowadays, data are generated in a continuous streaming manner as the inputs of various applications. The sources of such generated data can be wired or wireless sensor networks commonly used in various fields of geographical, traffic, Internet of Things (IoT), financial tickers, Web2 and Web3, ecommerce, social networks, and online communities. The high volume, high variety, and high velocity of data have recently posed the challenge of 3Vs to this field, also known as the Big Data Problem. The 3Vs dimensions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 51 publications
0
8
0
2
Order By: Relevance
“…The Physical level refers to the physical storage and practical implementation in a database management system [10]. The physical structure of the database is the basis of the entire database storage, which is mainly determined in the design phase and is persistent, and once determined, the physical structure does not change frequently [11], Physical level design pertains to the process of structuring the storage of the logical model based on the characteristics of the chosen relational database.…”
Section: Physical Level Designmentioning
confidence: 99%
“…The Physical level refers to the physical storage and practical implementation in a database management system [10]. The physical structure of the database is the basis of the entire database storage, which is mainly determined in the design phase and is persistent, and once determined, the physical structure does not change frequently [11], Physical level design pertains to the process of structuring the storage of the logical model based on the characteristics of the chosen relational database.…”
Section: Physical Level Designmentioning
confidence: 99%
“…Although these databases have been evolving fast, they still have disadvantages: they are somewhat immature, and there is still no standardized language or interface for their use [9]. Some previous secondary studies have addressed design methods in the new era of databases [10], i.e., the existing challenges in NoSQL data storage in a distributed way [11], the new perspectives of NoSQL database design [12], as well as the data models for the Big Data problem [13]. However, no studies were found that synthesize, according to the type of database, the modeling procedures of these databases, the characteristics that said data must meet, and the characteristics of the management tools of those systems.…”
Section: Introductionmentioning
confidence: 99%
“…In [17], a systematic review of data models for the big data problem was presented concluding, among others, that a data model is required to define the data structure and storage as a way to meet the challenges of big data. Also, the article depicts the significance of data models even in databases that lack static data models and flexible schemas.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are a variety of data models with various purposes, there must be a logical structure or format for data storage even at the program level. This is evidence of the need for more focus and research on this issue [17]. In [18] the authors cover the evaluation of six open-source and eleven proprietary database modeling tools using a new and tailored approach.…”
Section: Introductionmentioning
confidence: 99%